Home in the woods - Wheeler, Eliza (New York : Nancy Paulsen Books, 2019)
During the Great Depression six-year-old Marvel, her seven siblings, and their mother find a tarpaper shack in the woods and, over the course of a year, turn it into a home. Based on the author's grandmother's childhood; includes historical notes.
Keywords: Families -- Juvenile fiction; Poverty -- Fiction; Single-parent families -- Fiction; Depressions -- 1929 -- Fiction; Families -- Fiction; Poverty -- Fiction; Single-parent families -- Fiction; Depressions -- 1929 -- Fiction; Families -- Fiction; Family life -- Fiction; United States -- History -- 1919-1933 -- Fiction; United States -- History -- 1919-1933 -- Fiction